Design and implementation of a 4D cadastral legal model for Turkish land administration infrastructure based on LADM - Surmeneli, Hicret Gursoy; Alkan, Mehmet; Koeva, Mila (TAYLOR & FRANCIS LTD, 2022)
This article discusses 3D cadastral objects registration with time attributes and implementation within the Turkish Land Administration Domain Model (LADM) framework. This research will discuss the practical pathway towards realizing LADM-based 3D cadastral objects registration and focuses on extending the representation of those cadastral objects to 4D (3D + t) with time attributes in alignment with the jurisdictional settings in Turkey. The prototype development begins with data modelling. Also, the data was managed in an open-source PostgreSQL database. The developed prototype can answer all questions about cadastral objects, such as property, right, restrictions and responsibility (RRR) types, temporal queries and spatial source document and usage type of cadastral objects. It has been anticipated that this study may serve as a model for other national authorities with similar land management systems, particularly cadastral objects with time-qualification records, including the existing Spatial Data Infrastructure (SDI) initiative in Turkey.
Keywords: 3D-4D cadastre; LADM; 3D database management system; PostgreSQL; spatial-temporal data; 3D; REPRESENTATION; IMPACT; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology